A Phenomenology of Closed Society in “The Drowned Girl” by Antanas Vienuolis: Anthropological Profiles - Jūratė Levina (Literatūra (Vilnius))
The inquiry formulates the fundamentals of the hermeneutics of narrative against the background of the history of reception of the work under examination, “The Drowned Girl” by Antanas Vienuolis, and draws on the relevant phenomenological descriptions and resources of structural analysis to foreground the operative mechanisms of closed society. Such mechanisms are foregrounded on three planes: (1) social, of the rules of relationships between people, which in the story constitute a hierarchal system of power relations modelled on the structure of the traditional family of the agricultural holding, (2) significative, comprising sense-making discourses (traditional customs and Christianity) whereby the culture, in this story, configures the world without transcending corporeally perceivable horizons of the actually lived present, and (3) anthropological, where sociocultural praxis and self-perception are grounded in the essentially unhuman nature which the culture tries to assimilate and erase without recognising its essential otherness. This threefold configuration emerges at the crossroad of the (author’s and reader’s) Modern and (the represented) archaic cultural self-conceptions, which produces the conflict of interpretations and facilitates both the cathartic effect and the ongoing process of sense-making. All these configurations are derived from the story’s poetics, simultaneously exposing the discursive operative mechanisms of closed society.